Investigation of ELF5, KIF18A, NPTX1 and COL23A1 genes in the pathophysiology of indirect inguinal hernia in children - Genc, Ercan; Tartar, Tugay; Onalan, Ebru; Bakal, Unal; Sarac, Mehmet; Kaymaz, Tugce; Kazez, Ahmet (Springer, 2026)
Purpose In this study, we investigated the effect of ELF5, KIF18A, NPTX1 and COL23A1 genes in residual processus vaginalis (PV) the main factor in the development of indirect inguinal hernia (IIH) in children. Methods Cases operated for IIH in children aged 0-18 years between 2018 and 2021 constituted the study group, and cases with undescended testis without hernia the control group. Protein levels of KIF18A, which has the highest gene expression in tissue samples, were also analyzed by ELISA method. Polymorphisms of ELF5, KIF18A and COL23A1 genes with the highest level of expression change in blood and tissue samples were analyzed by qRT-PCR. Statistical analysis was performed. Results There were 186 patients in the study group and 26 patients in the control group. The results of ELF5, KIF18A and COL23A1 genes were significantly higher in the study group than in the control group. There was a statistically significant positive correlation between GAPDH and ELF5, KIF18A and NPTX1 in the study group. Also, a statistically significant positive correlation was found between KIF18A and ELF5 and between NPTX1 and ELF5 and COL23A1. Conclusion The present study may be the first study conducted in human tissue samples that we could access in the literature in terms of the genetic factors. It was predicted that ELF5, KIF18A and COL23A1 genes may be counted among the effective factors in PV closure. This study may shed light on larger prospective genetic studies.
Keywords: Inguinal hernia; Etiology; Genetics; Polymorphism; Pediatric